Ceramic Papers as Structured Catalysts: Preparation and Application for Particulate Removal - Leonardi, Sabrina Antonela (2022)
Fibers represent a type of structure of great interest in catalysis since they combine high area to volume ratio and can be fabricated from many types of materials, such as ceramic oxides, polymers, and alloys. They can be used in isolated form or structured, as in the case of the ceramic papers synthesized in this work, following a modified papermaking technique. The addition of cationic and anionic polyelectrolytes improved the retention of ceramic fibers during the ceramic paper formation stage by adsorption processes, through the formation of floccules. In the complex aqueous system containing charged macromolecules, the amounts of polyelectrolytes to be added were determined by titrations. To enhance mechanical properties of ceramic papers, different classes of nanoparticle suspensions can be used as binders. As a novel alternative, we have used different borate-type compounds. Among them, we selected natural ulexite, which was purified and used as a binder of ceramic fibers. In order to improve mechanical resistance and flexibility, measured from tensile indexes and elastic module, the amounts of NaCaB5O6(OH)6.5H2O and the calcination temperature were varied. In this contribution, to take advantage of the unique characteristics of the ulexite-containing ceramic papers, they were impregnated with Co,Ce and Co,Ba,K and tested for diesel soot combustion.